1988
DOI: 10.1203/00006450-198801000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Control of Water Balance in Infants with Bronchopulmonary Dysplasia: Role of Endogenous Vasopressin

Abstract: ABSTRACT. Babies with chronic bronchopulmonary dysplasia (BPD) can sometimes develop pallor, systemic and pulmonary edema, oliguria, and hyponatremia not attributable to cardiopulmonary or renal impairment. These signs and symptoms might, however, be explained by inappropriate control of vasopressin secretion. To test this hypothesis, we measured plasma vasopressin and osmolality, serum sodium and potassium concentrations, urine output and osmolality, and free water clearance in 26 normoxic infants with BPD ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
1

Year Published

1989
1989
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 16 publications
2
19
1
Order By: Relevance
“…Kojima et al [2] demonstrated that AVP levels were higher in LBW infants, regardless of whether or not they had bronchopulmonary dysplasia (BPD), compared to term infants suggesting that AVP levels may be influenced by maturity at birth or birthweight. In contrast, Hazinski et al [1] did not find a relationship between AVP levels and gestational age in BPD infants nor was any correlation demonstrated between AVP levels and maturity in cord samples [14]. The infants in this study who went on to develop CLD were significantly more immature and tended to be lighter than the non-CLD infants.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…Kojima et al [2] demonstrated that AVP levels were higher in LBW infants, regardless of whether or not they had bronchopulmonary dysplasia (BPD), compared to term infants suggesting that AVP levels may be influenced by maturity at birth or birthweight. In contrast, Hazinski et al [1] did not find a relationship between AVP levels and gestational age in BPD infants nor was any correlation demonstrated between AVP levels and maturity in cord samples [14]. The infants in this study who went on to develop CLD were significantly more immature and tended to be lighter than the non-CLD infants.…”
Section: Discussioncontrasting
confidence: 49%
“…In such infants the elevated AVP levels were associated with hyponatraemia and fluid restriction [1,2]. Mechanical ventilation [3], pneumothorax [3,4] and infection [3], all risk factors for the development of CLD, are also associated with raised AVP levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these symptoms are similar to those seen in patients with SIADH (4, 5). Recently, Hazinski et al (2) found that some infants with chronic BPD have elevated plasma AVP levels and they speculated the functional significance of these elevated values. However, all these articles are about water balance in the chronic stage of BPD.…”
mentioning
confidence: 99%
“…It presumably results from the direct renal effects of furosemide, but it may also involve drug effects on the secretion of prolactin (25), vasopressin (26), or atrial natriuretic peptide. The mobilized water arises from the interstitial compartment and is not limited to pulmonary IW.…”
Section: Discussionmentioning
confidence: 99%